Application of Dasylab in Teaching Electrical Engineering - Ptak, Paweł (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The teaching of subjects connected with electricity, such as electrotechnics or electronics is an important part of school and technical university curricula. Due to the recent development of computer technology, laboratory exercises can be performed through simulation. Such simulations can be performed in a virtual environment measurement. The paper presents an example simulation process of a measuring system in the software environment DasyLab.